1
$\begingroup$

Prove $x^{rs}-1=(x^s-1)(x^{s(r-1)}+x^{s(r-2)}+...+x^s+1)$

I can see that this is true for simple results such as $x^6$ and $x^9$

How can I prove that this is true in general.

$\endgroup$
2
$\begingroup$

It telescopes. From $$(x^s-1)(x^{s(r-1)}+x^{s(r-2)}+...+x^s+1)$$ consider $$x^s \times(x^{s(r-1)}+x^{s(r-2)}+...+x^s+1) - (x^{s(r-1)}+x^{s(r-2)}+...+x^s+1)$$ The first term becomes $$(x^{sr}+x^{s(r-1)}+...+x^{2s}+x^s)$$ which just leaves $$x^{sr}-1$$

$\endgroup$
3
$\begingroup$

This is equivalent to the geometric series formula: $$1+y+y^2+\cdots+y^n={y^{n+1}-1\over y-1}$$ and therefore $$(y-1)(1+y+y^2+\cdots+y^n)=y^{n+1}-1$$. Substituting $y=x^s$ and $n=r-1$ we obtain your formula.

If you require a proof of the geometric series formula, see for instance this question and any of the answers (I recommend mine :P, but they're mainly pretty good).

$\endgroup$
0
$\begingroup$

Hint

Let $x^s=y$. Use Ruffini's rule to divide $(y^r-1)/(y-1)$. Finally undo the previous assignment (that is, let $y=x^s$ back again).

$\endgroup$
0
$\begingroup$

Hint

Set $y=x^s$, then $y=1$ is solution of $$y^r-1=0$$ and thus, you can factorise $y^r-1$ by $(y-1)$ what gives $$y^r-1=(y-1)(y^{r-1}+y^{r-2}+...+y+1).$$

$\endgroup$
0
$\begingroup$

Observe $1+x^s+x^{2s}+\ldots+x^{(r-1)s}$ is the sum of the first $r$ terms of a geometric sequence, and then it is equal to $(1-(x^s)^r)/(1-x^s)$ or $(x^{sr}-1)/(x^s-1)$.

$\endgroup$
0
$\begingroup$

Start with $x^r-1=(x-1)(x^{r-1}+\cdots+x+1)$. Write this identity for $x=y^s$. This gives keeping in mind that $(y^s)^r=y^{rs}$ $$\begin{align} y^{sr}-1=&(y^s-1)(y^{s(r-1)}+\cdots+y^s+1)\end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.